Originally Posted by
kjchauhan (1) Pl Note that,
$\displaystyle \frac{dy}{dx}=\frac{dy}{dt} \cdot \frac{dt}{dx}$
$\displaystyle \therefore \frac{dy}{dx}=\frac{(x-1)(y-1)}{-y(y-1)}$
$\displaystyle \therefore y \cdot dy= -(x-1) \cdot dx$
$\displaystyle \therefore y \cdot dy+(x-1) \cdot dx = 0$
Now integrate..
Same way,,,
(2)
$\displaystyle \frac{dy}{dx}=\frac{dy}{dt} \cdot \frac{dt}{dx}$
$\displaystyle \therefore \frac{dy}{dx}=\frac{y}{x)}$
$\displaystyle \therefore \frac{dy}{y}= \frac{dx}{x}$
Now integrate..